PERANAN R. A. A. WIRANATAKUSUMAH V DALAM PENYEBARAN TEMBANG SUNDA CIANJURAN - Mohamad Yusuf Wiradiredja (LP2M ISBI Bandung, 2012)
The main problems studied in this article is how the creation process of the art of cianjuran music and how far the role of R. A. A. Wiranatakusumah V in spreading the art of cianjuran music in Priangan in the 20th century. To get the answers to those problems, the historical research has been done with the method of research which consists of four phases: heuristik, criticism, interpretation, and historiography. The application of historical method is then ellaborated with social science theories, among of those is the theory of change and continuity of K. J. Veeger.The result of the research indicates that the art of cianjuran music was born as a creativity result of Cianjur aristocratics adopting from some vocal arts among Sundanese society such as: poetry, degung, and kawih. In its growth, the art of cianjuran adapts with the change of epoch so that its existence can be kept well. In this case, R. A. A. Wiranatakusumah V had an important role in spreading the art of cianjuran music in Priangan.Â Keywords: Cianjuran Music, R. A. A. Wiranatakusumah VÂ